Merancang Sistem Informasi Kantin Mbak Bet Universitas Muhammadiyah Riau Untuk Meningkatkan Promosi - Raifan, Farel; Daud, Daudi; Sundari , Fitriani; Kartika, Fakhri Nazif (Jurnal Inovasi Teknologi Terapan, 2024)
The Muhammadiyah Riau University Canteen "Mbak Bet" has been operating for 14 years since 2010.  This canteen provides a variety of food and beverage menus to meet the needs of campus residents. However, the large number of competitors, limited promotions, and uncertain class schedules cause customers who come to the campus canteen to vary every day, making it difficult to predict income. Based on these problems, the purpose of this research is to create an information system that can increase promotion. The system designed is based on a website that can be accessed by customers and canteen owners. The method used is linear sequential. The result of this research is a canteen information system that contains canteen profile information, menus, and promos. The implementation of this system is expected to help the canteen in promoting the menu and increasing customers.